2018
DOI: 10.1002/2017ja024839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Southern Hemisphere Sudden Stratospheric Warmings on Antarctica Mesospheric Tides: First Observational Study

Abstract: We analyzed the structure and variability of observed winds and tides in the Antarctica mesosphere and lower thermosphere (MLT) during the 2002 major sudden stratospheric warming (SSW) and the 2010 minor SSWs. We noted the effect of SSW on the variability of MLT tides for the first time in the Southern Hemisphere, although it has been well recognized in the Northern Hemisphere. We utilized the winds measured by Rothera (68°S, 68°W) medium frequency radar and King Sejong Station (62.22°S, 58.78°W) meteor radar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…However, similar studies for the SH are by far fewer than for the NH (Eswaraiah et al, 2018). A handful of studies have investigated the MLT thermal structure and dynamics during the 2002 major SSW (e.g., Cho et al, 2004; Dowdy et al, 2004) and in the 2010 minor SSW in the SH (Eswaraiah et al, 2016, 2017, 2018). Aside from the 2010 minor SSW, a minor SSW was noticed in 1988 in the SH, but it was fainter than the 2010 SSW (Kanzawa & Kawaguchi, 1990; de Laat & van Weele, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, similar studies for the SH are by far fewer than for the NH (Eswaraiah et al, 2018). A handful of studies have investigated the MLT thermal structure and dynamics during the 2002 major SSW (e.g., Cho et al, 2004; Dowdy et al, 2004) and in the 2010 minor SSW in the SH (Eswaraiah et al, 2016, 2017, 2018). Aside from the 2010 minor SSW, a minor SSW was noticed in 1988 in the SH, but it was fainter than the 2010 SSW (Kanzawa & Kawaguchi, 1990; de Laat & van Weele, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Since the first observational evidence of the mesosphere response to the SSWs (Quiroz, 1969), numerous studies have been made on the mesosphere coupling with the polar stratosphere during the SSW in the NH high and midlatitudes (e.g., Charlton & Polvani, 2007; de Wit et al, 2015; Medvedeva et al, 2019). However, similar studies for the SH are by far fewer than for the NH (Eswaraiah et al, 2018). A handful of studies have investigated the MLT thermal structure and dynamics during the 2002 major SSW (e.g., Cho et al, 2004; Dowdy et al, 2004) and in the 2010 minor SSW in the SH (Eswaraiah et al, 2016, 2017, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, a record stratospheric warming event occurred over Antarctica in September 2019 (Lim et al, 2020;Yamazaki et al, 2020). A handful of studies have investigated the thermal structure and dynamics of the mesosphere and lower thermosphere during the 2002 major SSW (e.g., Dowdy et al, 2004;Shepherd et al, 2005) and the 2010 minor SSW (Eswaraiah et al, 2016(Eswaraiah et al, , 2017(Eswaraiah et al, , 2018. However, the studies on the mesosphere response to the 2019 SH SSW are not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…and the temperature increased by about 30 K at 80 • S and 10 hPa (Eswaraiah et al, 2018). The zonal winds at 60 • S at 10 hPa weakened by only 20-25 m/s (Eswaraiah et al, 2016).…”
mentioning
confidence: 93%